Characterization of Planar Based Electrode Piezoelectric Micromachined Ultrasonic Transducer for Underwater Sensor Application using FEA Simulation - Khairul Azman Ahmad; Mohamad Faizal Abd Rahman; Noramalina Abdullah (Applications of Modelling and Simulation, 2020)
This paper presents a simulation and characterization of piezoelectric macromachined ultrasonic transducer (PMUT) based on planar electrodes. This small scale device with low power consumption is important as an underwater sensor. However, PMUT has a low sensitivity problem. Thus, PMUT based on planar electrodes are designed to improve the sensitivity of the PMUT. The designs are simulated using Finite Element Analysis (FEA) COMSOL Multiphysics 5.0. It is based on planar electrodes, cavity and multilayer membranes which can improve the transmitting and receiving sensitivity of ultrasonic transducer. The targeting application is for an underwater sensor with the range frequency in between 300 kHz to 800 kHz. Two characterizations are studied which are transmitting voltage response (TVR) and open circuit receiving response (OCRR). Three parameters are investigated namely the piezoelectric material, the thickness of PZT5H and electrode area. In simulation results, aluminium nitrate (AlN) has the highest in both TVR and OCRR. For the different PZT5H thicknesses, the highest transmitting sensitivity is obtained at the thickness of 300 μm meanwhile for highest receiving sensitivity is obtained at the thickness of 500 μm. It is found that the electrode area at 0.3 mm x 0.3 mm has the highest in both transmitting sensitivity and receiving sensitivity. Based on the targeted frequency design, PZT5H with a thickness of 200 μm and the electrode area of 0.5 mm x 0.5 mm is the most appropriate one.